Māori News is Bad News : That's certainly so on television - Moewaka Barnes, Helen; Nairn, Ray; Borell, Belinda; Gregory, Amanda; McCREANOR, TIMOTHY (MAI Journal, 2012)
A television news bulletin tells us, in effect, what we should think about and the preferred way in which we should think about it. Analyses of New Zealand media have consistently shown that news about Māori is both relatively rare and that it prioritises violence and criminality. Researchers conclude this encourages New Zealanders to see Māori as threatening the social order and burdening our society. We examined the few Māori stories broadcast in a large representative sample of English-language television news bulletins and found the same negativity. As our sample included Māori-language news bulletins from the same days we know there were other Māori news stories available, so we conclude that the prioritising of negative stories about Māori in English-language media is a matter of choice. Focus groups with Māori and non-Māori media consumers demonstrate the impact of the relentlessly negative portrayals of Māori in New Zealand media.

Anti-Maori themes in New Zealand journalism--toward alternative practice - Moewaka Barnes, Angela; Borell, Belinda; Taiapa, Ken; Rankine, Jenny; Nairn, Ray; McCreanor, Tim (Pacific Journalism Review, 2012)
Gale Academic OneFile includes Anti-Maori themes in New Zealand journalism--toward alt by Angela Moewaka Barnes, Belinda Borell, . Click to explore.
Keywords: health; media; privilege; racism; representation; wellbeing